Shelley : selected poems - Shelley, Percy Bysshe, 1792-1822.; Adamson, Carlene A.; Bowers, Will; Donovan, Jack; Duffy, Cian; Everest, Kelvin; Matthews, Geoffrey, 1920-1984; Nabugodi, Mathelinda; Pite, Ralph; Rossington, Michael (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Percy Bysse Shelley (1792 - 1822) was one of the major Romantic Poets and wrote what is critically recognised as some of the finest lyric poetry in the English Language. In this volume, the editors have selected the most popular, significant and frequently taught poems from the 6-volume Longman Annotated edition of Shelley's poems. Each poem is fully annotated, explained and contextualised, along with a comprehensive list of abbreviations, an inclusive bibliography of material relating to the text and interpretation of Shelley's poetry, plus an extensive chronology of Shelley's life and works. Headnotes and footnotes furnish the personal, literary, historical and scientific information necessary for an informed reading of Shelley's richly varied and densely allusive verse, making this an ideal anthology for students, classroom use, and anyone approaching Shelley's poetry for the first time; however the level and extent of commentary and annotation will also be of great value for researchers and critics"--
"This volume presents a substantial selection from the complete Poems of Shelley published in the Longman Annotated English Poets series in six volumes (1989-2022)."
Keywords: Poetry; LITERARY CRITICISM / General